Modern Physics - Tipler, Paul A.; Llewellyn, Ralph A. (New York: W H Freeman, 2003)
This new edition combines pedagogy, problem sets, and teaching art in a presentation that includes coverage of a number of new topics and discoveries. It features problems divided by level of difficulty; offers valuable grounding in the history of the field; accommodates both one and two term courses and allows instructors to vary the applications topics covered from term to term; uses real data, photographs of people and apparatus, and quotations from original papers; covers "relativity" in two chapters, enabling instructors to teach just the basics or go deeper without disturbing continuity; has "exploring" sections throughout which deal with very current topics and/or topics of high student interest; and includes a new chapter, "Astrophysics and Cosmology", which is featured on the Modern Physics Web Site, complete with dramatic colour photos, and links to astronomy and astrophysics research sites worldwide. There are also nearly 500 figures and drawings and extensive end-of-chapter media references. These annotated references point to exceptional, carefully reviewed experiments, simulations, and other noteworthy material that is generally available and easy to use. Instructors can decide which programs and media offerings suit their course. These references will be updated often on the book's Web site.
Includes bibliographical references.; Appendix A-F, AP1-AP39p.
Keywords: Physics